The Students’ Difficulties in Reading Comprehension at The Second Semester (A2) FKIP in Batanghari University Jambi Academic Year 2021 - Kartika Dewi (Universitas Batanghari Jambi, 2022)
In this researcher centers on the troubles in reading comprehension by the second semester of students ‘of FKIP in Batanghari University. In this plan, analyst utilized quantitative method. Subject of the analyst is students’ second semester (A2). The researcher used Purposive sampling to select the sample consists of 10 students. There was just only one class of the second semester. The technique of collecting data was by using a test by multiple choice consisted of 20 question items and questionnaire with Likert scale was utilized to gather information. Based on the finding of students’ reactions in questionnaire, they were with score weak criterion. The researcher it can be concluded that the most under studies had trouble in Reading Comprehension. Furthermore, Reading Comprehension test only two students got high scores 90. And Average 49, 5. It is demonstrates that the students have troubles in answering reading comprehension test The researcher it can be concluded that the most students had difficulty in Reading Comprehension. It is recommended that to have a great of perusing comprehension, understudies ought to learn more approximately the perusing comprehension and continuously perusing English content such as perusing aptitudes and doing hone perusing test.